Sulfide-based all-solid-state battery material and sulfide-based all-solid-state battery

By combining the polyether material with the ring-shaped structure backbone with the sulfide solid electrolyte, the problem of reduced electrolyte reactivity in the sulfide battery is solved, high ionic conductivity and stability are achieved, and the performance of the all-solid state battery is improved.

JP2025059530APending Publication Date: 2025-04-10OSAKA SODA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169673
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

In the prior art, the reaction between the sulfide solid electrolyte and the polymer electrolyte causes the ionic conductivity of the sulfide solid electrolyte layer to decrease, and such reaction is not effectively suppressed.

Method used

Polyether (polyether) material with a ring-shaped structure backbone is used as the electrolyte component. By combining with the sulfide solid electrolyte, its reactivity is suppressed, thereby improving the performance of the sulfide-based all-solid battery.

Benefits of technology

The reaction between polyether and sulfide electrolyte is effectively suppressed, high ionic conductivity is maintained, and the performance and stability of the sulfide-based all-solid-state battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059530000001
    Figure 2025059530000001
  • Figure 2025059530000002
    Figure 2025059530000002
Patent Text Reader

Abstract

To provide a sulfide-based all-solid-state battery material that suppresses reactions in a sulfide solid electrolyte.SOLUTION: It has been found that a sulfide-based all-solid-state battery material containing a polyether with a cyclic structure in the main chain suppresses the reactivity of a sulfide solid electrolyte.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sulfide-based all-solid-state battery material and a sulfide-based all-solid-state battery using the sulfide-based all-solid-state battery material. [Background technology]

[0002] Conventionally, non-aqueous electrolyte secondary batteries, such as lithium ion batteries, use electrolytes in the form of a solution or paste in terms of ionic conductivity. However, various safety measures are required to prevent leakage of the electrolyte, which may damage the device, and this is an obstacle to the development of large-scale batteries.

[0003] In response to this, all-solid-state lithium-ion secondary batteries using sulfide solid electrolytes have been proposed. A solid electrolyte can be obtained by dispersing the sulfide solid electrolyte and an organic binder in an organic solvent to prepare a slurry solution, which is then coated and dried. However, the organic binder does not have lithium ion conductivity, and there is a problem that the ion conductivity of the solid electrolyte layer decreases when it is combined with the organic material.

[0004] As a method for imparting lithium ion conductivity to an organic binder, a method of compounding a polymer solid electrolyte consisting of a polymer and a Li electrolyte salt is known. Polyethylene oxide, which has relatively high ion conductivity, is mainly used as the polymer of the polymer solid electrolyte, but it is known from literature that polyethylene oxide and a sulfide solid electrolyte react and deteriorate, and the ion conductivity of the composite solid electrolyte decreases. For this reason, Patent Document 1 reports an example of using a composite solid electrolyte in which an oxide solid electrolyte and a polymer solid electrolyte are compounded, but no example of compounding with a sulfide solid electrolyte is reported, and no method of suppressing the reaction between polyether and a sulfide solid electrolyte is proposed. In addition, Patent Document 2 reports a composite solid electrolyte consisting of a sulfide solid electrolyte and a polymer solid electrolyte, and an all-solid-state lithium ion secondary battery using them, but the sulfide solid electrolyte and the polymer solid electrolyte exist as separate solid electrolyte layers, and no example of a battery using a composite solid electrolyte consisting of a single layer, which is more likely to be reactive, has been reported. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2020 / 110994 [Patent Document 2] Patent Publication No. 2022-40100 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has as its main object the provision of a material for a sulfide-based all-solid-state battery that inhibits the reaction of a sulfide solid electrolyte, and further has as its object the provision of a sulfide-based all-solid-state battery that includes the material for a sulfide-based all-solid-state battery. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that a sulfide-based all-solid-state battery material containing a polyether having a cyclic structure in its main chain suppresses the reactivity of a sulfide solid electrolyte. The present invention has been completed based on this finding and further research.

[0008] That is, the present invention provides the following aspects. Item 1: A sulfide-based all-solid-state battery material containing a polyether having a cyclic structure in the main chain. Item 2. The sulfide-based all-solid-state battery material according to Item 1, further comprising a lithium salt compound. Item 3. The sulfide-based all-solid-state battery material according to Item 1, which is a composite solid electrolyte with a sulfide inorganic solid electrolyte. Item 4. A sulfide-based all-solid-state battery comprising the sulfide-based all-solid-state battery material according to any one of items 1 to 3. Effect of the Invention

[0009] The present invention is useful because it suppresses the reactive deterioration between the polyether and the sulfide solid electrolyte, thereby reducing the risk of deterioration of the performance of a sulfide-based all-solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention relates to a sulfide-based all-solid-state battery material containing a polyether having a cyclic structure in the main chain. In this specification, a numerical value connected with "~" means a numerical range including the numerical values ​​before and after "~" as the lower limit and upper limit. When multiple lower limit values ​​and multiple upper limit values ​​are listed separately, any lower limit value and upper limit value can be selected and connected with "~".

[0011] Specifically, the polyether having a cyclic structure in the main chain is a polyether having a structural unit derived from an alicyclic epoxide which may have a substituent, and / or a structural unit (A) derived from a heterocyclic epoxide which may have a substituent. The alicyclic epoxide and the heterocyclic epoxide are preferably 5- to 8-membered rings, and more preferably 5- to 6-membered rings. The heterocyclic epoxide preferably has a nitrogen atom or an oxygen atom in the ring, and is particularly preferably an oxygen atom. Examples of the substituent that can be substituted include alkyl groups such as methyl, ethyl, and isopropyl, aryl groups such as phenyl, aralkyl groups such as benzyl, unsaturated hydrocarbon groups such as vinyl groups, halogeno groups such as fluoro groups, chloro groups, bromo groups, and iodo groups, amino groups, and nitro groups. The polyether having a cyclic structure in the main chain may be crosslinked.

[0012] Examples of structural units derived from alicyclic epoxides and structural units derived from heterocyclic epoxides include structural units derived from compounds such as 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 3,4-epoxytetrahydrofuran, 3-(bromomethyl)-6-oxabicyclo[3.1.0]hexane, 3-(benzyloxy)-6-oxabicyclo[3.1.0]hexane, 3-benzyl-7-oxa-3-azabicyclo[4.1.0]heptane, 4-methyl-1,2-cyclohexene oxide, 1-methyl-1,2-epoxycyclohexane, 1,2-epoxy-4-vinylcyclohexane, triethoxy[2-(7-oxabicyclo[4.1.0]heptan-3-yl)ethyl]silane, 8-oxabicyclo[5.1.0]octane, and 1,2-epoxycyclooctane. The structural unit derived from an alicyclic epoxide and the structural unit derived from a heterocyclic epoxide may be composed of structural units derived from one type of monomer, or may be composed of structural units derived from two or more types of monomers.

[0013] In the polyether, the molar ratio of the constituent unit derived from an alicyclic epoxide which may have a substituent and / or the constituent unit (A) derived from a heterocyclic epoxide which may have a substituent is preferably 30 to 100 mol %, more preferably 50 to 100 mol %, and particularly preferably 70 to 100 mol %.

[0014] The polyether having a cyclic structure in the main chain may be a copolymer having a structural unit (B) derived from an alkylene oxide, preferably a structural unit derived from an alkylene oxide having 2 to 18 carbon atoms, more preferably a structural unit derived from an alkylene oxide having 2 to 8 carbon atoms, and particularly preferably a structural unit derived from an alkylene oxide having 2 to 4 carbon atoms (ethylene oxide, propylene oxide, butylene oxide). The structural unit (B) derived from an alkylene oxide having 2 to 18 carbon atoms may be composed of structural units derived from one type of monomer, or may be composed of structural units derived from two or more types of monomers.

[0015] In the polyether, the molar ratio of the structural unit (B) derived from an alkylene oxide is preferably from 0 to 70 mol %, more preferably from 0 to 50 mol %, and particularly preferably from 0 to 30 mol %.

[0016] The polyether having a cyclic structure in the main chain may be a copolymer having a structural unit (C) derived from a monomer represented by formula (1). [ka] [In formula (1), R represents a group containing an ethylenically unsaturated group.]

[0017] Examples of the structural unit (C) derived from a monomer of formula (1) include structural units derived from monomers such as allyl glycidyl ether, 4-vinylcyclohexyl glycidyl ether, α-terpinyl glycidyl ether, cyclohexenyl methyl glycidyl ether, p-vinylbenzyl glycidyl ether, allyl phenyl glycidyl ether, vinyl glycidyl ether, 3,4-epoxy-1-butene, 3,4-epoxy-1-pentene, 4,5-epoxy-2-pentene, 1,2-epoxy-5,9-cyclododecanediene, 3,4-epoxy-1-vinylcyclohexene, 1,2-epoxy-5-cyclooctene, glycidyl acrylate, glycidyl methacrylate, glycidyl sorbate, glycidyl cinnamate, glycidyl crotonate, and glycidyl-4-hexenoate. Preferred are structural units derived from monomers such as allyl glycidyl ether, glycidyl acrylate, glycidyl methacrylate, etc. The structural unit derived from the monomer of formula (1) may be composed of structural units derived from one type of monomer, or may be composed of structural units derived from two or more types of monomers.

[0018] In the polyether, the molar ratio of the structural unit (C) derived from the monomer represented by formula (1) is preferably from 0 to 10 mol %, and more preferably from 0 to 5 mol %.

[0019] In the polyether, when all the constituent units are taken as 100 mol %, the total of the constituent units derived from an alicyclic epoxide which may have a substituent and / or the constituent units derived from a heterocyclic epoxide which may have a substituent (A), the constituent units derived from an alkylene oxide (B), and the constituent units derived from the monomer represented by formula (1) (C) is preferably 80 to 100 mol %, more preferably 90 to 100 mol %, and may be 100 mol %. The molar ratio of each constituent unit is 1 It is determined by H-NMR spectroscopy.

[0020] The polyether may contain structural units other than the structural unit derived from an alicyclic epoxide which may have a substituent and / or the structural unit derived from a heterocyclic epoxide which may have a substituent, the structural unit (B) derived from an alkylene oxide, and the structural unit (C) derived from a monomer represented by formula (1), and the content of these structural units is preferably 0 to 20 mol %, and more preferably 0 to 10 mol %.

[0021] The weight-average molecular weight of the polyether having a cyclic structure in the main chain is not particularly limited, but may be 10,000 to 4 million, more preferably 50,000 to 3 million, particularly preferably 100,000 to 2.5 million, and may be 100,000 to 2 million. The weight-average molecular weight is calculated by gel permeation chromatography (GPC) using dimethylformamide (DMF) or tetrahydrofuran (THF) as a solvent in terms of standard polystyrene.

[0022] The synthesis of polyethers having a cyclic structure in the main chain can be carried out, for example, as follows. A catalyst system based on organoaluminum, a catalyst system based on organozinc, a catalyst system based on organotin-phosphate ester condensate, or other coordinate anion initiator, or a catalyst system based on K as a counter ion, is used as a ring-opening polymerization catalyst. + Polyether (i) can be obtained by reacting each monomer with an anionic initiator such as potassium alkoxide containing potassium alkoxide, diphenylmethyl potassium, or potassium hydroxide in the presence or absence of a solvent at a reaction temperature of 10 to 120° C. under stirring. From the viewpoint of the degree of polymerization or the properties of the resulting copolymer, a coordinated anionic initiator is preferred, and among them, a catalyst system mainly based on an organic zinc or an organotin-phosphate ester condensate catalyst system is particularly preferred because of its ease of handling.

[0023] The sulfide-based all-solid-state battery material preferably contains a lithium salt compound in addition to the polyether having a cyclic structure in the main chain. As the lithium salt compound, a lithium salt compound having a wide potential window, such as that generally used in lithium ion batteries, is suitable. Examples of the lithium salt compound include, but are not limited to, LiBF4, LiPF6, LiClO4, LiCF3SO3, LiN(CF3SO2)2(LiTFSI), LiN(SFO2)2(LiFSI), LiN(C2F5SO2)2, and LiN[CF3SC(C2F5SO2)3]2. These may be used alone or in a mixture of two or more. In addition, a form containing a polyether having a cyclic structure in the main chain and a lithium salt compound can be described as a polymer electrolyte.

[0024] When the sulfide-based all-solid-state battery material contains lithium chloride, the content thereof, expressed as the mole number of lithium salt compound / the total mole number of ether oxygen atoms of polyether having a cyclic structure in the main chain, is preferably in the range of 0.0001 to 5, and more preferably in the range of 0.001 to 0.5.

[0025] The sulfide-based all-solid-state battery material may be used as a composite solid electrolyte with a sulfide solid electrolyte.

[0026] The sulfide solid electrolyte used in the sulfide-based all-solid-state battery material of the present invention is not particularly limited, as long as it contains sulfur, has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation. For example, a lithium ion conductive solid electrolyte that satisfies the composition represented by the following formula can be used. Li a M b P c S d A e In the formula, M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. Among them, B, Sn, Si, Al, and Ge are preferable, and Sn, Al, and Ge are more preferable. A represents I, Br, Cl, and F, and I and Br are preferable, and I is particularly preferable. a to e represent the composition ratio of each element, and a:b:c:d:e satisfies 1-12:0-1:1:2-12:0-5. a is more preferably 1-9, and more preferably 1.5-4. b is more preferably 0-0.5. d is more preferably 3-7, and more preferably 3.25-4.5. e is more preferably 0-3, and more preferably 0-2.

[0027] In the formula, the composition ratios of Li, M, P, S and A may be such that b and e are 0, b=0, e=0 and the ratio of a, c and d (a:c:d) is a:c:d=1-9:1:3-7, or b=0, e=0 and a:c:d=1.5-4:1:3.25-4.5.

[0028] The sulfide solid electrolyte may have a crystalline sulfide solid electrolyte, and the crystal structure of the crystalline sulfide solid electrolyte may be an argyrodite crystal structure. An example of the argyrodite crystal structure is the Li7PS6 crystal structure, which is represented by Li7-xPS6-xHax (Ha is Cl or Br, and x is preferably 0.2 to 1.8). The Li7PS6 structure may have a Li7PS6 structural skeleton, and a portion of P may be substituted with Si.

[0029] Specific examples of sulfide-based solid electrolytes include Li2S / SiS2, Li2S-SiS2 / P2S5, Li2S / P2S5, Li2S / GeS2, Li2S / GeS2 / Ga2S3, Li2S / B2S3, Li2S / Ga2S3, Li2S / Al2S3, Li2S / GeS2 / P2S5, Li2S / Al2S3 / P2S5, Li2S / P2S3, Li2S / P2S3 / P2S5, Li2S / SiS2 / Li4SiO4, Li2S / SiS2 / Li3PO4, LiX / Li2S / P2S5, LiX / Li2S / SiS2, LiX / Li2S / B2S3 (X is a halogen atom (Br, Cl or I)), and the like.

[0030] When the sulfide solid electrolyte is in the form of particles, the particle size is, for example, 0.01 to 100 μm, and preferably 0.1 to 20 μm.

[0031] In the sulfide-based all-solid-state battery material of the present invention, the mass ratio of the sulfide solid electrolyte to the polyether having a cyclic structure in the main chain is not particularly limited, but from the viewpoint of more suitably exhibiting excellent charge / discharge characteristics in a solid electrolyte secondary battery, the polyether having a cyclic structure in the main chain is preferably 0.1 to 1000 parts by mass, more preferably 0.5 to 500 parts by mass, even more preferably 1 to 400 parts by mass, still more preferably 2 to 200 parts by mass, and particularly preferably 4 to 100 parts by mass, relative to 100 parts by mass of the sulfide solid electrolyte.

[0032] The sulfide-based all-solid-state battery material of the present invention may contain a known thickener. Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose and their salts (alkali metal salts such as sodium salts, ammonium salts), polyvinyl alcohol, polyacrylates, polyethylene oxide, and the like. These thickeners may be used alone or in combination of two or more. The content of the thickener may be 0.1 to 5 parts by mass, and preferably 0.2 to 3 parts by mass, relative to 100 parts by mass of the total of the polyethers having a cyclic structure in the main chain.

[0033] The sulfide-based all-solid-state battery material of the present invention can be formed into a sheet. When the complex sulfide-based all-solid-state battery material of the present invention is applied to a solid electrolyte secondary battery, the thickness is not particularly limited, but may be, for example, about 0.01 to 1 mm, preferably about 0.02 to 0.8 mm, and more preferably about 0.03 to 0.6 mm.

[0034] Method for producing sulfide-based all-solid-state battery materials The sulfide-based all-solid-state battery material of the present invention can be prepared by utilizing a conventionally known method. For example, it can be produced by a method of dispersing a sulfide solid electrolyte in a solvent containing a polyether (and a lithium salt compound, if necessary) having a cyclic structure in the main chain to prepare a slurry for a sulfide-based all-solid-state battery material, spraying and drying the slurry in hot air to obtain a composite solid electrolyte, or by heating and evaporating the solvent of the dispersion slurry under atmospheric pressure or reduced pressure to dryness, or by applying the dispersion slurry to a current collecting sheet or the like and drying it.

[0035] As the dispersion solvent, an organic solvent can be used. Whether the obtained dispersion slurry is a homogeneous solution or the solute that is not dissolved in the dispersion solvent is a sulfide solid electrolyte and / or a polyether having a cyclic structure in the main chain, it can be prepared by the above-mentioned general preparation method. It is desirable to remove as much remaining solvent and moisture as possible from the sulfide-based all-solid-state battery material obtained by removing the dispersion solvent. For example, this can be achieved by evacuating the material under vacuum for 1 to 48 hours under heating at 30°C to 200°C. Since the dried sulfide-based all-solid-state battery material of the present invention has ion conductivity and binding properties, the electrolyte powder itself can be pressure-molded and used as a solid electrolyte material. Furthermore, by performing a pressure heat treatment, the porosity can be reduced and the particle interface adhesion can be increased. As the organic solvent, a non-polar solvent that has low reactivity with the sulfide solid electrolyte is preferable. Specifically, toluene, xylene, butyl butyrate, ethyl propionate, butyl propionate, anisole, isobutyronitrile, dibutyl ether, diisobutyl ketone, etc. are used alone or in mixture. When a sulfide solid electrolyte is molded alone under pressure, it has almost no adhesiveness, resulting in a thick electrolyte film. However, in the case of a composite solid electrolyte, the adhesiveness of the polyether having a cyclic structure in its main chain makes it possible to manufacture a thinner solid electrolyte.

[0036] Crosslinking of sulfide-based all-solid-state battery materials In the sulfide-based all-solid-state battery material, by crosslinking the polyether having a cyclic structure in the main chain, the binding strength between the sulfide solid electrolyte in the sulfide-based all-solid-state battery material and the polyether having a cyclic structure in the main chain can be increased, and also short-circuiting of the battery due to restraining pressure or precipitation of dendrites can be prevented. As a crosslinking method, crosslinking can be performed by applying heat or irradiating with active energy rays such as ultraviolet rays.

[0037] In the case of crosslinking by heat, a radical initiator selected from organic peroxides, azo compounds, etc. is used. As the organic peroxide, ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxyesters, etc., which are usually used for crosslinking, are used, and as the azo compound, azonitrile compounds, azoamide compounds, azoamidine compounds, etc., which are usually used for crosslinking, are used. The amount of radical initiator added varies depending on the type, but is usually within the range of 0.1 to 10 parts by mass, assuming that the polyether having a cyclic structure in the main chain is 100 parts by mass.

[0038] In the case of crosslinking by irradiation with active energy rays, alkylphenones, benzophenones, acylphosphine oxides, titanocenes, triazines, bisimidazoles, oxime esters, etc. are used as radical initiators. The amount of these radical polymerization initiators to be added varies depending on the type, but is usually within the range of 0.01 to 5.0 parts by mass based on 100 parts by mass of polyether having a cyclic structure in the main chain.

[0039] In the present invention, when crosslinking the sulfide-based all-solid-state battery material, a crosslinking assistant may be used. As the crosslinking assistant, ethylene glycol diacrylate, ethylene glycol dimethacrylate, oligoethylene glycol diacrylate, oligoethylene glycol dimethacrylate, trimethylolpropane triacrylate, allyl methacrylate, allyl acrylate, diallyl maleate, triallyl isocyanurate, maleimide, phenylmaleimide, maleic anhydride, etc. can be arbitrarily used.

[0040] Sulfide-based all-solid-state battery comprising a sulfide-based all-solid-state battery material An example of a sulfide-based all-solid-state battery comprising the sulfide-based all-solid-state battery material of the present invention is a sulfide-based all-solid-state battery comprising a positive electrode, a negative electrode, and a composite solid electrolyte obtained by combining a polyether having a cyclic structure in its main chain with a sulfide solid electrolyte as the sulfide-based all-solid-state battery material. The composite solid electrolyte is disposed between the positive electrode and the negative electrode.

[0041] Known electrodes can be used for both the positive electrode and the negative electrode, and an example of the electrode is an electrode having an electrode material layer, that is, a positive electrode material layer or a negative electrode material layer, on a current collector.

[0042] Known current collectors can be used for the positive and negative electrodes. Specifically, metals such as aluminum, nickel, stainless steel, gold, platinum, and titanium are used as the current collector for the positive electrode. Metals such as copper, nickel, stainless steel, gold, platinum, and titanium are used as the current collector for the negative electrode.

[0043] The positive electrode material layer and the negative electrode material layer each contain at least a positive electrode active material and a negative electrode active material, and may further contain a conductive assistant, a binder, and a thickener, and may contain the above-mentioned sulfide solid electrolyte as necessary.

[0044] The positive electrode active material used in the present invention is a lithium metal-containing composite oxide powder having any one of the compositions LiMO2, LiM2O4, Li2MO3, and LiMEO4. Here, M in the formula is mainly composed of a transition metal and contains at least one of Co, Mn, Ni, Cr, Fe, and Ti. M is composed of a transition metal, but in addition to the transition metal, Al, Ga, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc. may be added. E contains at least one of P and Si. The particle diameter of the positive electrode active material is preferably 50 μm or less, and more preferably 20 μm or less. These active materials have an electromotive force of 3 V (vs. Li / Li+) or more.

[0045] Specific examples of the positive electrode active material include lithium cobalt oxide, lithium nickel oxide, nickel / cobalt / lithium manganese oxide (ternary system), spinel-type lithium manganese oxide, and lithium iron phosphate.

[0046] The negative electrode active material used in the present invention is a carbon material (natural graphite, artificial graphite, amorphous carbon, etc.) having a structure (intercalation compound) capable of absorbing and releasing alkali metal ions such as lithium ions, or a metal such as lithium, an aluminum-based compound, a tin-based compound, a silicon-based compound, or a titanium-based compound capable of absorbing and releasing alkali metal ions such as lithium ions. In the case of a powder, the particle size is preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 20 μm or less. A mixed active material of a metal and a carbon material may also be used.

[0047] When a conductive assistant is used, a known conductive assistant can be used, and examples thereof include conductive carbon black such as graphite, furnace black, acetylene black, and ketjen black, carbon fibers such as carbon nanotubes, and metal powder. One or more of these conductive assistants may be used. When a conductive assistant is used, the content of the conductive assistant is not particularly limited, but the upper limit is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less, relative to 100 parts by mass of the total amount of the active material. The lower limit of the content of the conductive assistant is usually 0.05 parts by mass or more, 0.1 parts by mass or more, 0.2 parts by mass or more, 0.5 parts by mass or more, and 2 parts by mass or more.

[0048] The binder may be, for example, one or more compounds selected from fluororesins such as PVdF, fluororubbers, acrylic rubbers, modified acrylic rubbers, styrene-butadiene rubbers, acrylic polymers, vinyl polymers, and the polyethers described above. These binders are added in an amount of preferably 5 parts by mass or less, more preferably 4 parts by mass or less, for example 0.01 to 3 parts by mass, based on 100 parts by mass of the active material.

[0049] Specific examples of the thickener include carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, ethylcellulose and their salts (alkali metal salts such as sodium salts, ammonium salts), polyvinyl alcohol, polyacrylates, polyethylene oxide, etc. These thickeners may be used alone or in combination. These thickeners are added in an amount of preferably 5 parts by mass or less, more preferably 3 parts by mass or less, for example 0.01 to 2 parts by mass, based on 100 parts by mass of the active material. In addition, when the viscosity of the coating liquid is low, a thickener can be used in combination.

[0050] The method for producing the positive and negative electrodes having the current collector, the positive electrode material layer, and the negative electrode layer is not particularly limited, and a general method is used. For example, the method is performed by uniformly applying a paste (coating liquid) of the positive and negative electrode materials, which are composed of the positive and negative electrode active materials, the conductive assistant, the binder, the solvent such as tetralin, butyl butyrate, and anisole, and if necessary, the thickener, on the surface of the current collector to an appropriate thickness by the doctor blade method, the silk screen method, or the like.

[0051] For example, in the doctor blade method, negative and positive active material powders, conductive additives, binders, etc. are dispersed in a solvent to form a slurry, which is then applied to a metal electrode substrate and uniformized to an appropriate thickness using a blade with a specified slit width. After the active material is applied to the electrode, it is dried, for example, with hot air at 100°C or under reduced pressure at 80°C to remove excess organic solvent. After drying, the electrode is press-molded using a press device to produce the electrode.

[0052] Method for manufacturing sulfide-based all-solid-state battery comprising sulfide-based all-solid-state battery material The method for producing a sulfide-based all-solid-state battery comprising the sulfide-based all-solid-state battery material of the present invention is not particularly limited, and the battery is composed of a positive electrode, a negative electrode, and a composite solid electrolyte, and is produced by a known method. For example, in the case of a laminated lithium ion battery, a laminated body composed of a positive electrode, a composite solid electrolyte, and a negative electrode is produced, and leads are connected to the positive and negative electrodes, and then the battery is vacuum sealed using a laminated packaging material or the like. The shape of the battery is not limited, and examples include a laminated type, a coin type, a cylindrical type, and the like, and may be a structure in which two or more batteries are stacked. EXAMPLES

[0053] The present invention will be described in more detail in the following examples, but is not limited thereto.

[0054] In this example, a composite material (composite solid electrolyte) was produced using a sulfide solid electrolyte and a polymer, and the following evaluations were performed.

[0055] [Weight average molecular weight of polyether] Gel permeation chromatography (GPC) was performed, and the weight average molecular weight was calculated based on standard polystyrene. In the examples, GPC was performed at 40°C using Shimadzu Corporation's RID-20A, Showa Denko Corporation's Showdex KF-806L, KF-803L and KF-801 columns, and THF as a solvent. In the comparative examples, GPC was performed at 60°C using Shimadzu Corporation's RID-10A, Showa Denko Corporation's Showdex KD-807, KD-806, KD-806M and KD-803 columns, and DMF as a solvent.

[0056] [Evaluation of the composite material] To evaluate the composite material, a SUS blocking cell of a composite material of sulfide solid electrolyte and polymer was fabricated, and an AC impedance test was performed using a potentio / galvanostat device.

[0057] AC Impedance Test A SUS blocking cell of the composite material was prepared and an AC impedance test was performed using a potentio / galvanostat device (device name: SP-300 manufactured by BioLogic). The resistance (Ω) of the composite material was calculated from the diameter of the real axis of the semicircular arc obtained from the Cole-Cole plot. In addition, the ionic conductivity of the cell was calculated from the thickness and surface area of ​​the cell using the following formula. σ = 1 / R × (d / A) σ: Ionic conductivity of the composite material (S / cm) R: Resistance of the composite material (Ω) d: thickness of composite material (cm) A: Surface area of ​​the composite material (cm 2 ) The test temperature was set to 25° C. The measurements were performed with a voltage amplitude of 20 mV and a measurement frequency range of 7 MHz to 100 mHz.

[0058] [Polymerization Example 1 Polymer 1] The inside of a 200mL glass eggplant flask was replaced with nitrogen, and 11.2g of 1,2-epoxycyclopentane with a moisture content of 10ppm or less and 44.8g of n-hexane as a solvent were charged. 0.12g of pure water was added to this, and then 6.7mL of 1mol / L diethylzinc hexane solution was added as a polymerization catalyst to carry out the polymerization reaction. The polymerization temperature was 35°C, and the reaction was carried out for 24 hours. 2.6g of the polymer obtained by air-drying the reaction solution for 20 hours was dissolved in 130mL of THF and centrifuged at 3750rpm for 30 minutes. The supernatant was concentrated with an evaporator, and then dried under reduced pressure at 40°C for 5 hours to obtain 0.6g of a purified polymer. The obtained polymer was a homopolymer of 1,2-epoxycyclopentane (PCP) and had a weight average molecular weight of 320,000.

[0059] [Comparative Polymerization Example 1 Polymer 2] As the polymerization catalyst, the polymerization catalyst used in the section of the Examples of Japanese Patent No. 4923946 (JP Patent Publication 2008-106104) was produced. The inside of a 3L glass four-neck flask was replaced with nitrogen, and 1g of the above catalyst and 125g of ethylene oxide as the polymerization catalyst, 5.0g of tert-butyl alcohol adjusted to a moisture content of 10 ppm or less, and 1000g of n-hexane as the solvent were charged therein, and 125g of ethylene oxide was added successively while tracking the polymerization rate by gas chromatography. The polymerization temperature was set to 20°C, and the reaction was carried out for 10 hours. The polymerization reaction was stopped by adding 1mL of methanol. The polymer was taken out by decantation, air-dried for 20 hours, and further dried under reduced pressure at 40°C for 5 hours to obtain 230g. The obtained polymer was a homopolymer of polyethylene oxide (PEO) and had a weight average molecular weight of 1.17 million.

[0060] [Preparation of Composite Material Example 1] A polymer solution was prepared by dissolving the polymer 1 obtained in Polymerization Example 1 in toluene, which is a dispersion medium (solid content concentration: 5% by mass). An argyrodite-type sulfide solid electrolyte (NEI, LPSCl (Li6PS5Cl)) was mixed with this polymer solution so that the sulfide solid electrolyte:polymer ratio was 80:20 by mass to prepare a composite material slurry. The dispersion medium was removed from this slurry by vacuum heating and drying to obtain a composite material. This composite material was pulverized using a mortar, and a pelletizer and a flat plate press were used to prepare a powder compact of the composite material having a thickness of 500 to 600 μm.

[0061] [Preparation of composite material Comparative example 1] A powder molded product of the composite material was produced by the method described in Example 1, except that Polymer 1 obtained in Polymerization Example 1 was changed to Polymer 2 obtained in Polymerization Comparative Example 1.

[0062] [Example of AC impedance test for composite materials] A SUS blocking cell was prepared using the composite materials obtained in Example 1 and Comparative Example 1, and an AC impedance test was carried out. After a heat treatment at 60°C for 24 hours, an AC impedance test was carried out again to confirm the change in ionic conductivity. The results are shown in Table 1.

[0063] From the above-mentioned ionic conductivity measurement, the ionic conductivity of Example 1 using PCP did not decrease by heat treatment, whereas the ionic conductivity of Comparative Example 1 using PEO decreased by heat treatment. In Comparative Example 1, the sulfide solid electrolyte reacted with PEO by heat treatment, but no significant deterioration was observed in Example 1, confirming that PCP has excellent sulfide stability.

[0064] [Table 1] [Industrial Applicability]

[0065] A sulfide-based all-solid-state battery material containing a polyether having a cyclic structure in its main chain is useful because it is unlikely to deteriorate the performance of a sulfide-based all-solid-state battery by suppressing the reaction deterioration with the sulfide solid electrolyte, and can be suitably used for large battery applications such as in-vehicle applications such as electric vehicles and hybrid electric vehicles, and storage batteries for home power storage.

Claims

1. A sulfide-based all-solid-state battery material containing polyether with a cyclic structure in the main chain.

2. The sulfide-based all-solid-state battery material according to claim 1 , further comprising a lithium salt compound.

3. The sulfide-based all-solid-state battery material according to claim 1, which is a composite solid electrolyte with a sulfide inorganic solid electrolyte.

4. A sulfide-based all-solid-state battery comprising the sulfide-based all-solid-state battery material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • All-solid secondary battery

    JP2022040100A

  • Composite solid electrolyte, and composite solid electrolyte secondary battery

    WO2020110994A1